The cell biology of major histocompatibility complex class I assembly: towards a molecular understanding - Hateren, Andy van; James, Ed; Bailey, Alistair; Phillips, Andrew; Dalchau, Neil; Elliott, Tim (Tissue Antigens, 2010)
Major histocompatibility complex class I (MHC I) proteins protect the host from intracellular pathogens and cellular abnormalities through the binding of peptide fragments derived primarily from intracellular proteins. These peptide-MHC complexes are displayed at the cell surface for inspection by cytotoxic T lymphocytes. Here we reveal how MHC I molecules achieve this feat in the face of numerous levels of quality control. Among these is the chaperone tapasin, which governs peptide selection in the endoplasmic reticulum as part of the peptide-loading complex, and we propose key amino acid interactions central to the peptide selection mechanism. We discuss how the aminopeptidase ERAAP fine-tunes the peptide repertoire available to assembling MHC I molecules, before focusing on the journey of MHC I molecules through the secretory pathway, where calreticulin provides additional regulation of MHC I expression. Lastly we discuss how these processes culminate to influence immune responses.